On the town [videorecording (DVD)] - Kelly, Gene, 1912-1996; Kelly, Gene, 1912-1996; Donen, Stanley; Sinatra, Frank, 1915-1998; Garrett, Betty, 1919-2011; Miller, Ann, 1923-2004; Bernstein, Leonard, 1918-1990; Bernstein, Leonard, 1918-1990 (Frank Sinatra collection (Turner Entertainment Co.), 2008)
Sailors Gabie, Chip, and Ozzie have a 24-hour leave in New York. Chip wants to sightsee, but the only sights Gabie and Ozzie are interested in are of the female variety.